2012 IEEE Second International Conference on Healthcare Informatics, Imaging and Systems Biology 2012
DOI: 10.1109/hisb.2012.65
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis of Physicians' EHR Workflow during Outpatient Visits

Abstract: We develop temporal data mining and visualization methods to quantitatively profile physician Electronic Health Records (EHR) workflow and compare time-at-task versus click count distributions for top-level EHR functionality. The temporal data is based on time-resolved activity during outpatient visits, captured by usability software and audiovideo recording and manual coding to physicians' activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Our software drives data collection from Kinect and Microcone, and it is designed to be extensible, allowing easy integration of additional sensors. 6 Figure 3 shows ChronoSense in action during a recording session. ChronoSense runs on any Windows machine that supports Kinect and Microcone.…”
Section: Morae Recorder (See Footnote 3) This Usabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Our software drives data collection from Kinect and Microcone, and it is designed to be extensible, allowing easy integration of additional sensors. 6 Figure 3 shows ChronoSense in action during a recording session. ChronoSense runs on any Windows machine that supports Kinect and Microcone.…”
Section: Morae Recorder (See Footnote 3) This Usabilitymentioning
confidence: 99%
“…What is needed are careful analyses of how the EHR is used by physicians during patient encounters and how physicians and patients communicate. Recent approaches [6] started to analyze and quantify speech, gaze, body movements, etc. and represent very promising ways to complement classic software usability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because structured and unstructured data can be hard to reconcile, EHRs often store and display information in separate pages or windows, and physicians have to synthesize the patient narrative by navigating across a variety of sources [3,44]. This creates increased cognitive burden to discover unstructured information, and studies have shown that clinicians spend more time reading past notes than doing any other activity in the EHR [12]. Further, the fragmented interfaces hinder comprehensibility and necessitate frequent taskswitching [15,31,63].…”
Section: Introductionmentioning
confidence: 99%